Best Answer

y = 8x + 15

5x - 3y = 12

Substitute 8x + 15 for y in the second equation:

5x - 3y = 12

5x - 3(8x + 15) = 12

5x - 24x - 45 = 12 add 45 to both sides:

-19x = 57 divide by -19 to both sides:

x = -57/19

Substitute -57/19 for x in the first equation:

y = 8x + 15

y = 8(-57/19) + 15

y = -456/19 + 15

y = [-456 + (15)(19)]/19

y = (-456 + 285)/19

y = -171/19

The solution is x = -57/19 and y = -171/19

Q: Solve by subsitution y equals 8x plus 15 5x-3y equals 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

x= 1/2

The GCF is 5xy.

How do you solve 4y plus x equals 8

-2 plus 5 equals +3

Not enough information to solve

A is 14

1

Px equals -0.6 plus 60x-1500

many solutions

5

a= -0.8

Can you help with this equation? Thanks. Solve for x and y and z for the following. x plus y plus z equals 9 x plus 2y plus 3z equals 23 x plus 5y plus -3z equals -7